2012
DOI: 10.3109/00365521.2012.722675
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein cytokines in the early phase of acute experimental oedematous and necrotizing porcine pancreatitis

Abstract: The initial inflammatory process was diverse in oedematous and necrotizing pancreatitis. Increased monocyte count in combination with elevated PDGF and IL-6 are characteristic of necrotizing pancreatitis in our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The progressive tissue damage at the cellular level of pancreatic tissue is the result of the cytokines and reactive oxygen species (ROS) secreted by the inflammatory cells [3,4]. Most studies investigating the early and chronic phases of the disease have emphasized the role of B and T lymphocytes, macrophages, neutrophils, cytokines, inflammation mediators, and reactive oxygen species (ROS) [11][12][13]. For this reason, various anti-inflammatory [14,15], antioxidant [4,15,16], and immunomodulatory [17] agents have been used in experimental studies for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive tissue damage at the cellular level of pancreatic tissue is the result of the cytokines and reactive oxygen species (ROS) secreted by the inflammatory cells [3,4]. Most studies investigating the early and chronic phases of the disease have emphasized the role of B and T lymphocytes, macrophages, neutrophils, cytokines, inflammation mediators, and reactive oxygen species (ROS) [11][12][13]. For this reason, various anti-inflammatory [14,15], antioxidant [4,15,16], and immunomodulatory [17] agents have been used in experimental studies for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies to date have monitored the levels of circulating Th9 cells or their infiltration into the pancreas in the context of AP. Furthermore, Merilainen et al [46] found no significant difference in serum IL-9 concentrations between experimental edematous and necrotizing pancreatitis groups and sham controls during the early course of AP. Therefore, further research is needed to clarify the potential role of Th9 cells in the pathogenesis of AP and their potential as a therapeutic target.…”
Section: Th9 Cellsmentioning
confidence: 95%
“…The finding of Th9 cells initiating immunity to helminth parasites indicates the possibility of these cells regulating immune responses in AP (Licona-Limón et al, 2013). In edematous and necrotizing porcine pancreatitis models, IL-9 levels in blood do not change compared with the sham group in the early phase (Merilainen et al, 2012). However, there have not been any reports on the number or function of Th9 cells involved in initiation or progression AP.…”
Section: Th9 Cellsmentioning
confidence: 98%